Preliminary development and evaluation of a mechanical handwriting assistive device to support individuals with movement disorders - Gabrielle Lemire; Gabrielle Lemire; Thierry Laliberté; Katia Turcot; Katia Turcot; Véronique H. Flamand; Véronique H. Flamand; Alexandre Campeau-Lecours; Alexandre Campeau-Lecours (Frontiers in Rehabilitation Sciences)
Individuals with movement disorders often face challenges in writing independently due to factors such as spasticity, lack of precise motor control, muscle weakness, and tremors. This paper aims to develop a handwriting assistive device (HAD) for individuals with movement disorders, to stabilize the motion of user's hand, through initial needs assessment, iterative design, and a preliminary evaluation. The research is scoped to include only initial testing with a small user group, six potential users with movement disorders, providing foundational insights for future refinement. The findings from the initial needs assessment revealed that current assistive technologies do not fully meet handwriting challenges for individuals with motor impairments. The HAD prototype, developed with adjustable damping mechanism and customizable handles to suit different levels of motor control, enabled steadier handwriting in preliminary testing with six participants. Children drew shapes more accurately, and some traced letters they couldn't otherwise. The adult participant showed greater fluidity and legibility, completing tasks 4.81 times faster with the HAD. The qualitative feedback indicated the device's potential to enhance handwriting independence and usability across age groups. Future prospects for this study include developing an electronic version of the HAD, allowing real-time adjustable damping to better support users' voluntary movements while further stabilizing involuntary motions.